2020
DOI: 10.1002/cjoc.201900532
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Hydrogen Nanoclusters: Atom‐Precise Model to Unveil Catalytic Mechanism and Growth Process of Gold Nanoparticles

Abstract: Gold nanoclusters show high catalytic performance in various chemical reactions including the hydrogenation and hydrogen evolution reactions. Hydrogen involved gold clusters is the ideal model to investigate the hydrogen-gold cluster interactions, the influence of H atoms on the electronic structures of the gold clusters, the particle growth process, and the catalytic mechanism. This paper highlights the pioneering experimental and theoretical works in the gold-hydrogen cluster studies, and overviews the exist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Hydride-containing metal nanoclusters are of particular interest because the hydride can be converted to H 0 , H + , or H 2 and then employed in catalysis. Among coinage metal clusters reported, several examples of copper and silver hydrido species exist; however, hydrido gold clusters are scarce . Tsukuda et al reported the synthesis of the [Au 9 (PPh 3 ) 8 H] 2+ superatom cluster via hydride doping of [Au 9 (PPh 3 ) 8 ] 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…Hydride-containing metal nanoclusters are of particular interest because the hydride can be converted to H 0 , H + , or H 2 and then employed in catalysis. Among coinage metal clusters reported, several examples of copper and silver hydrido species exist; however, hydrido gold clusters are scarce . Tsukuda et al reported the synthesis of the [Au 9 (PPh 3 ) 8 H] 2+ superatom cluster via hydride doping of [Au 9 (PPh 3 ) 8 ] 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…Monolayer‐protected metal nanoclusters (MPCs), as a new type of functional materials, have attracted broad research interest for decades. [ 1‐5 ] When the scale of nanomaterials is reduced to sub‐ten nanometer level, size effects appear. The continuous density of states breaks up into discrete energy levels, which translates into the unique optical, electrical, and chemical properties in comparison with nanoparticles.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…As will be shown here, the role of the hydride in the metal cluster is of particular importance and can play a variety of roles, depending on the metal type, nuclearity and geometry, and such conversions can be correlated, for example, to a typical energy or catalytic loop. [22][23][24] A fundamental issue is the ability to tune the structure and properties of the formed metal clusters -this can be done by a judicious choice in ligand selection and the design protocols of the metal clusters, all of which relies heavily on atomically precise structural (including neutron diffraction) information. Such investigations allow for an understanding how specific properties can be applied to perform certain functions.…”
Section: Introductionmentioning
confidence: 99%
“…but also related to the mechanisms to potentially explain the growth of clusters, and the subsequent formation of nanoparticles (NPs), wherein the hydrides are embedded in (interstitial) or ligated to the metal frameworks. As will be shown here, the role of the hydride in the metal cluster is of particular importance and can play a variety of roles, depending on the metal type, nuclearity and geometry, and such conversions can be correlated, for example, to a typical energy or catalytic loop [22–24] . A fundamental issue is the ability to tune the structure and properties of the formed metal clusters – this can be done by a judicious choice in ligand selection and the design protocols of the metal clusters, all of which relies heavily on atomically precise structural (including neutron diffraction) information.…”
Section: Introductionmentioning
confidence: 99%